Faktor Prediktif Prognosis Pasien dengan Ensefalopati Hipoglikemia - Debby Cinthya Damiri Valentina (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Severe hypoglycemia can cause damage to the brain resulting in a permanent coma. This condition is called hypoglycemic encephalopathy (HE). Hypoglycemic encephalopathy has various clinical outcomes, so several predictive values of physical examination as well as laboratory and radiologic investigations are needed to determine the prognosis of the disease. Methods: The method used in this literature review was by literature searches using inclusion and exclusion criteria. Then the steps of analyzing, synthesizing and summarizing were conducted in this literature review. Discussion: Hypoglycemic encephalopathy is diagnosed based on clinical findings in the state of stupor or coma which last ?24 hours despite the management of hypoglycemia. A history of previous illnesses must be explored such as the history of hypotension, hypertension, acidosis, drug intoxication, or infection. The diagnosis of HE must be done precisely by eliminating the possibility of other differential diagnosis through laboratory and radiological investigations. Radiological examination of cerebral MRI can show symmetrical hyperintense lesions in cerebral cortex, hippocampus, internal capsule, amygdala, or basal ganglia. The extent of the affected part of the brain is not significantly correlated to the patient's clinical outcome, so other predictive factors are needed to determine the prognosis of the disease. Predictive factors that can help in determining the prognosis of HE are body temperature, duration of hypoglycemia, blood glucose concentration, and lactic acid levels. Conclusion: History of illness and clinical symptoms along with laboratory and radiological examinations need to be carried out appropriately to diagnose HE and rule out other diagnoses. Thus, examination of predictive factors can be done to determine the prognosis of HE.